Revisiting the evolutionism of Edith Penrose's The theory of the growth of the firm: Penrose's entrepreneur meets Veblenian institutions - Felipe Almeida; Huáscar Pessali (EconomiA, 2017)
Edith Penrose's The theory of the growth of the firm has offered key ingredients to an evolutionary approach to the growth of the firm. The entrepreneur enlivened by Edith Penrose in that book is revisited here, considering the role played by institutions in his decision-making. It is argued that her view of the entrepreneur rests greatly in the task of successfully linking two intertwined institutional sets, one internal and the other external to the firm. As a result, the entrepreneur must deal with instrumental and ceremonial elements of both institutional sets in order to re-channel pecuniary gains. The evolutionary approach of Veblenian institutionalism offers an apt definition of institutions to the case in point and is thus used here to expand Penrose's case account of Hercules Powder Company. – – O livro “A teoria do crescimento da empresa” de Edith Penrose oferece uma abordagem evolucionária que discute os limites do crescimento da empresa. O empresário como analisado por Penrose, nesse livro, é revisitado neste artigo, considerando o papel desempenhado pelas instituiç\~oes em sua tomada de decis\~ao. É argumentado que pode-se identificar no empresário penroseano a funç\~ao de lidar com sucesso com dois conjuntos institucionais interligados, um interno e outro externo à empresa. Como resultado, o empresário deve lidar com elementos instrumentais e cerimoniais de ambos os conjuntos institucionais, a fim de gerar ganhos pecuniários. A abordagem evolucionária do institucionalismo vebleniano é a base teórica utilizada para analisar a relaç\~ao do empresário penroseano com instituiç\~oes. Esse artigo também apresenta uma releitura do relato de Penrose sobre a empresa Hercules Powder."
Keywords: 330; Edith Penrose; Institutions; Entrepreneur; Institutional entrepreneurship; Edith Penrose; Instituiç\~oes; Empresário; Empresário Institucional